Mekanisme Koping Pada Pasien Risiko Menciderai Orang Lain - Annas, Muhamad; , Arum Pratiwi, S.Kp., M.Kes (2017)
Background: The risk of violent behavior is a behave that the show by an individual where the individual tent to endanger themselves, others and their environment. Violent behavior is one of signs of mental disorder. The prevalence of mental illness is four to five of the 1000 population Indonesia include very severe mental disorder. Objective: The objective of the study is to understand how to apply nursing care of patients with violent behavior. Methods: The method of this study is case approach that applies nursing care on risk violent patient. Application comprised of assessment or interview, intervention, implementation and evaluation of nursing. Results: There were two included diagnoses are risk injuring, others and the environment associated with violent behavior and the risk of violent behavior associated with low self-esteem. Nursing care has been carried out for 3 days from December 20 to 22 February 2017 by using client approach strategy for violent behavior. After the nursing care performed showed the client is able to control violent behavior. Conclusion: Partnering with health care team, inadequate hospital facilities which are needed to determine the success of nursing care on the client so can be implemented way to control the violent behavior that has been taught nurses. Keywords: mental disorders, violent behavior, coping mechanisms